The rice seed industry in Thailand - Chaowagul, Makasiri (International Food Policy Research Institute, 2014)
This policy brief will provide an analysis of the maize seed industry’s current state and future prospects, prefacing that with a review of the historical context under which it emerged. Lessons learned from this sector could have implications for the development of the seed industry in other developing countries.